Framtidsfixarna - Bergquist, Magnus (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2001)
The paper deals with sensemaking about the future in the form of a growing business of trend analyses and scenario planning companies. The idea of "a new economy" is associated with turbulence and complexity in economic life, which opens up for a need for pointers towards plausible and strategic relevant futures scenarios. In order to become successful scenario planners first have to describe the present and unstable and then present their interpretation of future scenarios as possible or strategically relevant for their customers. Management sensemaking is thereby changed from formal analyses (based on tables and figures) to narrative visions in the form of intriguing stories. The good story-tellers become the management gurus in the new economy.